Quantitative assessment of flow between cerebrospinal and interstitial fluid compartments in humans - Anders Wåhlin; Sofia Behndig; Johan Eriksson De Ryst; Viktor Vigren Näslund; Daniel Dahlgren Lindström; Jan Axelsson; Cecilia Björnfot; Mikael Bylund; Anders Garpebring; Petter Holmlund; Afroditi Lalou; Klara Mogensen; et al. (Proceedings of the National Academy of Sciences, 2026)
According to glymphatic system theory, cerebrospinal fluid (CSF) perfuses the brain’s interstitial space to support waste clearance, but the magnitude of this flow and the outflow pathway of interstitial fluid (ISF) in humans remain uncertain. To achieve flow quantification, we applied a compartment-model approach applied in conjunction with serial quantitative MRI data acquired after intrathecal gadolinium administration. Using the method, we estimated CSF-to-ISF inflow to 45 ± 20 mL/h, in patients with suspected idiopathic normal pressure hydrocephalus. Tissue-specific contributions were 34 ± 14 mL/h in cortical gray matter, 11±6 mL/h in white matter, and 0.4 ± 0.3 mL/h in subcortical gray matter, suggesting that CSF perfusion occurs primarily in superficial regions near the subarachnoid space. A lack of correlation between inflow and total craniospinal system outflow (r = 0.03, P = 0.91) suggested that ISF recirculates back into CSF rather than exiting the craniospinal system via a separate route. Independent experiments in healthy older individuals using intravenous gadolinium administration supported ISF-to-CSF recirculation, where contrast material that presumably crossed the blood–brain barrier subsequently appeared in the subarachnoid space, allowing ISF-to-CSF flow quantification. These findings provide a quantitative framework for studying brain clearance in humans and support subarachnoid space recirculation as an important efflux route.